(untitled) - Kumar, Nirmalya (Boston, 2012)
India Inside provides a wake-up call for executives and policy makers in the developed world and a clear-eyed view of both the challenges and opportunities facing multinationals seeking new sources of innovation in the future.
Keywords: Technological innovations,New products,Đổi mới công nghệ,Sản phẩm mới; India,India,Ấn độ,Ấn độ